The effect of investment on economic growth in Gowa district - Linardi Linardi (Indonesia Accounting Research Journal, 2022)
Alam S, 2001. Economics. Third edition. Jakarta: PT Glora script pratama: Airlangga Amad Kamaruddin, 2006. Fundamentals of investment and portfolio management. Jakarta: PT Rineka Cipta Arifin, Zaenal. 2005. Theory of Finance and Capital Markets. First edition. Yogyakarta: Econesia Central Bureau of Statistics. 2009. Gowa Regency. BPS. Gowa in Figures Gowa in Figures 2009. Noor Faizal Henry, 2007. Manageral Economics. Jakarta : PT Raja Grafindo Persada. Ridwan (2004). Thesis Compiling Methods and Techniques. Second printing. Alphabet. Bandung. Rudianto, 2009. Budgeting. Jakarta: PT Gelora Aksara Pratama. Sadono Sukirno. 1994. Introduction to Macroeconomic Theory. Jakarta: PT RajaGrafindo Persada. Sugiono, Dr., Prof., (2010), Quantitative Qualitative Research Methods and R&D, Alfabeta, Bandung. Sukurno, Sadono. 1994. Introduction to Macroeconomic Theory. Second Edition. Jakarta: PT Raja Grafindo Persada. Sukurno, Sadono. 2000. Modern Macroeconomics. Jakarta: PT Raja Grafindo Persada. Tarigan, Robinson, MRP, . 2005. Regional Economic Theory and Applications. Jakarta: PT Bumi Aksara. Todaro, MP 2000. Economic Development in the Third World, Seventh Edition. Jakarta: Erlangga. Todaro, MP and Smith, SC 2006. Economic Development. Volume I. 9th Edition. Haris Munandar (translator). Jakarta: Erlangga.